Building A Smart Vehicle Registration Certificate Prototype Using RFID - Indrastanti R Widiasari; Arie Arie Setiawan Prasida; Dian W Chandra (Indonesian Journal of Computing and Modeling, 2019)
The Indonesian government requires a system capable of identifying vehicles since imposed restrictions on the use of subsidized fuel. This research aims to build a smart vehicle registration which allows a vehicle registration as a means of identifying the vehicles data wirelessly or contactless. Systems built using RFID technology. This study resulted in four prototype models developed into a smart vehicle registration certificate prototype (e-STNK).